ANALISIS DIMENSI SPIRITUALITAS DAN KEBERKAHAN DALAM TRADISI MENGHAFAL AL-QUR’AN DI PONDOK PESANTREN - Vivi Nur Maulidia; Muhammad Hasyim (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
This research analyzes the spiritual dimensions and blessings in the tradition of memorizing the Quran in Islamic boarding schools. Memorizing the Quran serves not only as a cognitive effort but also as a means to strengthen the spiritual connection of students with Allah SWT. Through interaction with the holy verses, students experience an increase in spirituality that impacts their character, discipline, and quality of life. This study employs a qualitative approach with a phenomenological method, involving in-depth interviews and observations to explore the experiences of students. The findings indicate that the blessings felt by students are closely related to their closeness to the Quran, which provides inner peace and ease in facing life's challenges. This research is expected to contribute to the development of more effective tahfidz learning methods in the boarding school environment.